Fatores associados a intensidade de dor perineal no pós parto vaginal: um estudo transversal - Santos, Caroline Cristina de Almeida (Universidade Federal de São Carlos, 2026)
Introduction: The presence and intensity of pain in the immediate postpartum period after vaginal birth may be influenced by multiple factors, including obstetric, sociodemographic, and clinical characteristics, as well as psychological aspects and social contexts. However, studies found in the literature often restrict the assessment to perineal trauma that may occur during childbirth and do not encompass other dimensions within the multidimensional context of pain. Objectives: To identify the presence and intensity of perineal pain, as well as its relationship with biological and social factors in women in the immediate postpartum period after vaginal delivery, and to assess perceived social support in this population. Methods: This is an observational cross-sectional study approved by the Research Ethics Committee of the Federal University of São Carlos (CAAE: 87569925.5.0000.5504). Women aged over 18 years, between 24 and 48 hours after vaginal delivery, hospitalized in a public maternity hospital in the city of São Carlos, Brazil, from May to August 2025, were included. The following instruments were used: a questionnaire with personal and clinical data of the postpartum women and previous and current obstetric history, the Perceived Social Support Scale, and the Numerical Pain Scale. Data were analyzed descriptively, and multiple linear regression analysis was performed to assess the association between biological and social factors and pain intensity. Results: The sample consisted of 93 participants, with a mean age of 27.20 (± 6.56) years, mean education level of 11.16 (± 2.26) years of schooling, 79.6% living with a partner, 54.8% being homemakers, 64.2% self-identified as Black, and a mean parity of 2.43 (± 1.48) children. The mean intensity of perineal pain reported by the women was 3.42 on the numerical pain scale. The variables correlated with pain were parity, race/skin color, pain when sitting, and pain when walking, all showing a negative direction. Regarding factors associated with pain intensity, only race/skin color (B = -1.203; p = 0.018) and the presence of pain when walking (B = -1.481; p = 0.010) significantly contributed to explaining the variability in perineal pain intensity. White women reported 1.2 points higher perineal pain than Black or Brown women. In addition, women who experienced pain when walking reported 1.5 points higher perineal pain at rest. The mean total score of the Perceived Social Support Scale was 5.65 points, considered moderate support. Conclusion: It was possible to verify that among the postpartum women included in this study, perineal pain in the immediate postpartum period was moderate. Biological and social characteristics such as parity and race/skin color, as well as postpartum activities such as pain when sitting and walking, were associated with pain intensity during hospitalization. Furthermore, White women showed higher pain intensity than Black and Brown women, and women who reported pain when walking had higher pain intensity at rest. Perceived social support was considered moderate in this group.
Factors associated with perineal pain intensity in the postpartum period after vaginal birth: a cross-sectional study
Keywords: Dor perineal; Puerpério imediato; Períneo; Assoalho pélvico; Fisioterapia; Perineal pain; Postpartum period; Perineum; Pelvic floor; Physical therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar